STRATEGI PENGEMBANGAN MADRASAH EFEKTIF MELALUI PENGEMBANGAN MODEL MANAJEMEN PEMBIAYAAN PENDIDIKAN MADRASAH BERBASIS ZISWA-SCHOOL LEVY - Zulfa, Umi (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2016)
AbstractTh is research was aimed at describing and explaining: (1) the implementation of Educational Financing Management at MI Ya BAKII Karangjengkol Kesugihan Cilacap, (2) analysis existing model of Educational Financing Management Based Ziswa-School Levy (Study at MI Ya BAKII Karangjengkol Kesugihan Cilacap and (3) to formulate conceptual Development Model of Educational Financing Management Based Ziswa-School Levy. Th is research to study existing objectives by using a qualitative approach and research and development from Borg and gall. Th e object of this research was the implementation of Educational Financing Management Based Ziswa-School Levy and its conceptual Development Model of Educational Financing Management Based Ziswa-School Levy in MI Ya BAKII Karangjengkol Kesugihan. Th e data were obtained by conducting a direct observation in the ? eld, in-depht interviews and documentation. The technique of data analysis was qualitative analysis of the interactive model. Th e result of the research show that: the implementation of educational financing management at MI Ya BAKII Karangjengkol Kesugihan Cilacap so acuntable, and not yet utilization ziswa as educational financing sources its rich, and sustainable.Keyword: Strategy, management, school.